Beban kognitif, literasi AI, dan prokrastinasi akademik mahasiswa doktor: Tinjauan konseptual - Annisa Ciptagustia; Eeng Ahman; Edi Suryadi; Rofi Rofaida; Murni Zarina Mohamed Razali (Curricula: Journal of Curriculum Development, 2026)
Research on doctoral students is still fragmented in the study of Cognitive Load Theory (CLT), academic procrastination, and Artificial Intelligence (AI) literacy. This article integrates these three fields to explain the interaction between cognitive load, AI literacy competency, and academic procrastination in the context of doctoral students with dual roles in the era of generative AI. Using an integrative conceptual paper approach and a systematic search in the Scopus database (254 final articles: 58 CLT, 56 procrastination, 140 AI literacy), we found that none of the three streams connected all three constructs simultaneously. Five integrative propositions were formulated, namely (P1) cognitive load as a causal antecedent of procrastination; (P2) AI literacy as a moderator of the CLT-procrastination relationship; (P3) Self-Regulated Learning (SRL) and self-efficacy as dual mediators; (P4) dual-role as a cognitive load amplifier; and (P5) intellectual procrastination or the paradox of AI competence without adequate SRL. This article contributes to postgraduate curriculum design by offering five curricular components that are based directly on the identified causal mechanisms.